TNFα blockade overcomes resistance to anti-PD-1 in experimental melanoma. Issue 1 (December 2017) - Bertrand, Florie; Montfort, Anne; Marcheteau, Elie; Imbert, Caroline; Gilhodes, Julia; Filleron, Thomas; Rochaix, Philippe; Andrieu-Abadie, Nathalie; Levade, Thierry; Meyer, Nicolas; Colacios, Céline; Ségui, Bruno
Abstract Antibodies against programmed cell death-1 (PD-1) have considerably changed the treatment for melanoma. However, many patients do not display therapeutic response or eventually relapse. Moreover, patients treated with anti-PD-1 develop immune-related adverse events that can be cured with anti-tumor necrosis factor α (TNF) antibodies. Whether anti-TNF antibodies affect the anti-cancer immune response remains unknown. Our recent work has highlighted that TNFR1-dependent TNF signalling impairs the accumulation of CD8+ tumor-infiltrating T lymphocytes (CD8+ TILs) in mouse melanoma. Herein, our results indicate that TNF or TNFR1 blockade synergizes with anti-PD-1 on anti-cancer immune responses towards solid cancers. Mechanistically, TNF blockade prevents anti-PD-1-induced TIL cell death as well as PD-L1 and TIM-3 expression. TNF expression positively correlates with expression of PD-L1 and TIM-3 in human melanoma specimens. This study provides a strong rationale to develop a combination therapy based on the use of anti-PD-1 and anti-TNF in cancer patients. Most melanoma patients do not respond to anti-PD1 therapy. Here, the authors show that TNFα blockade synergizes with anti-PD-1 by preventing anti-PD-1-induced CD8+ T cell death and TIM-3 expression on such cells.